Renoprotective Effects of Melatonin in Young Spontaneously Hypertensive Rats with L-NAME - Ming-Chou Cheng; Ting-Hsin Wu; Li-Tung Huang; You-Lin Tain (Pediatrics and Neonatology)
Nitric oxide (NO) deficiency occurs in humans and animals with hypertension and chronic kidney disease (CKD). An inhibitor of NO synthase, NG-nitro-l-arginine methyl ester (L-NAME) exacerbates kidney damage in the adult spontaneously hypertensive rat (SHR). We examined whether L-NAME exacerbated hypertensive nephrosclerosis in young SHRs and whether melatonin protects SHRs against kidney damage by restoration of the asymmetric dimethylarginine (ADMA)–NO pathway. Methods: Rats aged 4 weeks were randomly assigned into three groups (n = 10 for each group): Group 1 (control), SHRs without treatment; Group 2 (L-NAME), SHRs received L-NAME (80 mg/L) in drinking water; and Group 3 (L-NAME + melatonin), SHRs received L-NAME (80 mg/L) and 0.01% melatonin in drinking water. All rats were sacrificed at 10 weeks of age. Results: L-NAME exacerbates the elevation of blood pressure, renal dysfunction, and glomerular sclerosis in young SHRs. L-NAME induced an increase of ADMA and a decrease of arginine-to-ADMA ratio in the SHR kidney. Melatonin therapy prevented L-NAME-exacerbated hypertension and nephrosclerosis in young SHRs. In addition, melatonin restored L-NAME-induced reduction of dimethylarginine dimethylaminohydrolase (DDAH; ADMA-metabolizing enzymes) activity in the SHR kidney. Next, melatonin decreased renal ADMA concentrations, increased renal arginine-to-ADMA ratio, and restored NO production in L-NAME-treated young SHRs. Moreover, melatonin reduced the degree of oxidative damaged DNA product, 8-hydroxydeoxyguanosine immunostaining in L-NAME-treated SHR kidney. Conclusion: Our results indicated that L-NAME/SHR is a useful model for hypertensive nephrosclerosis in young rats. The blood pressure-lowering and renoprotective effects of melatonin is due to increases of DDAH activity, decreases of ADMA, and reduction of oxidative stress in L-NAME-treated SHR kidney. Specific therapy targeting the DDAH–ADMA pathway may be a promising approach to slowing chronic kidney disease progression in children.